1953
DOI: 10.1002/path.1700660116
|View full text |Cite
|
Sign up to set email alerts
|

The histological changes in the adrenal of the hypophysectomised rat after treatment with pituitary preparations

Abstract: THE activity of adrenocorticotropic hormone (ACTH) may be estimated by three methods :-(1) Adrenal repair or maintenance in the hypophysectomised rat, based upon adrenal weight (Moon, 1936-37 ; Simpson et al., 1943). (2) Histological appearances-the repair of the sudanophobe zone which appears in the hypophysectomised rat (hiss et al., 1936-37). (3) The depletion of the ascorbic-acid content of the adrenal of the hypophysectomised rat one hour after the injection of ACTH (Sayers et al., 1948).St,ack-Dunne and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1955
1955
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Some authors found little or no effect (Cater & Stack-Dunne 1953Bransome & Reddy 1961), others reported an increase in DNA content (Farese & Reddy 1963;Imrie et al 1965;Masui & Garren 1970). In vitro investigations on cells from both the decapsulated adrenal and the gland capsule showed an inhibition of DNA synthesis by ACTH, that is, an inversed relationship between functional and proliferative activities (Ramachandran & Suyama 1975;Ramachandran et al 1977).…”
Section: Discussionmentioning
confidence: 93%
“…Some authors found little or no effect (Cater & Stack-Dunne 1953Bransome & Reddy 1961), others reported an increase in DNA content (Farese & Reddy 1963;Imrie et al 1965;Masui & Garren 1970). In vitro investigations on cells from both the decapsulated adrenal and the gland capsule showed an inhibition of DNA synthesis by ACTH, that is, an inversed relationship between functional and proliferative activities (Ramachandran & Suyama 1975;Ramachandran et al 1977).…”
Section: Discussionmentioning
confidence: 93%
“…In vivo, ACTH does not exhibit the same steroidogenic potency on zona glomerulosa and zona fasciculata. For instance, it is well established that hypophysectomy decreases the volume of zona fasciculata, without affecting the zona glomerulosa (Cater & Stack-Dunne 1953), while ACTH treatment increases the overall volume of the cortex (Mazzocchi et al 1986) and vascularization (Thomas et al 2003(Thomas et al , 2004. From these observations, we raised the hypothesis that the nature of extracellular matrix (ECM) and integrins could influence cell responses to ACTH, as also observed in the human foetal adrenal gland (Chamoux et al 2002).…”
Section: Introductionmentioning
confidence: 91%
“…For instance, in vivo, a sodium-deficient diet increases cell proliferation and width of the zona glomerulosa. On the other hand, hypophysectomy decreases [3], while ACTH treatment increases, adrenal gland volume [4] and vascularization.…”
Section: Introductionmentioning
confidence: 96%